Superparamagnetic iron oxide nanoparticles and essential oils: a new tool for biological applications - Miguel, Maria (2020)
Essential oils are complex mixtures of volatile compounds with diverse biological properties. Antimicrobial activity has been attributed to the essential oils as well as their capacity to prevent pathogenic microorganisms from forming biofilms. The search of compounds or methodologies with this capacity is of great importance due to the fact that the adherence of these pathogenic microorganisms to surfaces largely contributes to antibiotic resistance. Superparamagnetic iron oxide nanoparticles have been assayed for diverse biomedical applications due to their biocompatibility and low toxicity. Several methods have been developed in order to obtain functionalized magnetite nanoparticles with adequate size, shape, size distribution, surface, and magnetic properties for medical applications. Essential oils have been evaluated as modifiers of the surfacemagnetite nanoparticles for improving their stabilization but particularly to prevent the growth of microorganisms. This review aims to provide an overview on the current knowledge about the use of superparamagnetic iron oxide nanoparticles and essential oils on the prevention of microbial adherence and consequent biofilm formation with the goal of being applied on the surface of medical devices. Some limitations found in the studies are discussed.